Glycogen content in the eggs of four freshwater teleostean species - Basu, Sajal (Indian Journal of Fisheries, 2011)
Yolk begins to deposite in the egg during the period of vitellogenesis (Raven 1961, Kirpichnikov 1981). According to Balinsky (1970), yolk is first synthesized in the liver and then transported in the soluble state through the blood stream to the ovary for deposition in the mature oocytes. The essential components of yolk are proteins, phospholipids, glycogen and some neutral fats. Importance of glycogen in the normal development of a vertebrate embryo is well known (Spratt 1955,1958a). In the fish egg, this glycogen also acts as the substrate for various enzymes for glycolysis and other carbohydrate metabolism (Milman and Jurovtizsky 1973, Shaklee and Whitt 1967). As early development of eggs depends much on their energy source, the importance of glycogen in the fish egg needs due weightage. With this view the glycogen contents of the eggs of 4 teleostean species Mystus vittatus (Bloch), Notopterus notopterus (Pallas), Channa punctatus (Bloch) and Channa striatus (Bloch) were studied and histochemical tests of glycogen of the 4 species were also done. Mature eggs and ovaries